FORMULASI DAN UJI IRITASI SEDIAAN LULUR KRIM CANGKANG SOTONG (Sepia sp.) TERHADAP KELINCI (Oryctolagus cuniculus) - Arifin, Arfiani; Ida, Nur; Rosmiyanti, Rosmiyanti (Jurnal Riset Kefarmasian Indonesia, 2023)
Cuttlefish shell (Sepia sp.) contains calcium carbonate which has benefits in removing dead skin cells, regulating skin pigmentation, shrinking pores, removing acne and black spots and making skin brighter. The aims of this study were to formalize dosage form of cuttlefish shell cream scrub (Sepia sp.) that meets the physical quality requirements and to determine the potential irritation of cuttlefish shell (Sepia sp.) cream scrubs in rabbits (Oryctolagus cuniculus). Reseacrh methods include the dosage form of cuttlefish shell powder using sieve mesh 44, cream scrub formulations with variations in cuttlefish shell powder concentrations by 15%, 20% and 25%. Physical quality test carried iut includes organoleptic tests, homogeneity tests, scatter power tests and sticking power tests. The cream scrub formula irritation test was carried out by patch test method in rabbit test animals. The results of the study obtained that cuttlefish shell cream scrubs have qualified physical quality tests and the degree of irritation value of F1 cream scrubs (cuttlefish shell 15%) of 0,2 which is categorized means very mild irritation.